Pengaruh Latihan Ladder drill: Ladder Speed Run dan In Out Drill Terhadap Peningkatan Kecepatan dan Kelincahan - jendry alvin tefu (Jendela Olahraga, 2019)
AbstractThe purpose of this research is to improve the ability of speed and agility with the method of ladder speed run and in out drill. Samples of the student's research is the son of SMA Negeri 1 Soe who follow football and futsal ektrakurikuler activity with the number of the subject of 33 people. Type of this research is quantitative research with experimental approach is quasi (quasi-circling). The research design used was matching only design and data analysis using Anova and t-Test. Data retrieval using sprint 30 meters to measure the speed and agility of the t-test to measure agility at the time of pretest and posttest. Unit in measuring the speed and agility is second. The research was carried out for 6 weeks and is done three times a week. Research results show that the difference between the mean pretest and posttest of each group. Based on the data retrieved can be inferred that there is an increase in the speed and agility to each group after being given exercise Ladder Speed Run and In Out Drill as seen from test-t. In addition, through the test anova, which exercise Ladder Drill: Ladder Speed Run and In Out Drill gives significant influence than the control group.Keywords: Ladder Drills, Ladder, Run In Sped Out Drills, speed, agility